Estudo do potencial bioativo da fração clorofilada da biomassa de Phormidium autumnale - Nogara, Gabriela Predebon (2016)
Microalgae are recognized sources of metabolites with high added value, largely by biological activity of these compounds. Several species of cyanobacteria produce secondary metabolites with bioactive character due to its molecular structure. Currently studying a lot about pigments for its biological value, giving emphasis on its bioactivity, but chlorophyll is still poorly understood. Despite its important biological role, research on chlorophyll and its potential antioxidant and pro-oxidant are still scarce. The lack of information can be attributed to the difficulty of obtaining chlorophyll and its derivatives in a purified form and also to their instability, which triggers a process of degradation. Many uncertainties still exist in the scientific field of the natural chlorophyll, their metabolites, impact on health, due to its high content in some vegetables, widespread occurrence in nature, and its degradation during food processing and human digestion. The production of compounds of chlorophyll by microalgae, due to their diverse metabolism, makes biomass microalgal an alternative source, with different chemical structures as compared to conventional food matrix, and its complex system of conjugated bonds on pyrrole rings enables an antioxidant character, or pro-oxidative, acting in scavenging free radicals or reactive triggering systems of molecular degradation. In this sense, the study of these chlorophyll pigments designed to further focus on their chemical structure may help to elucidate the real potential bioactive these substances. Given the various chlorophyllous structures present in Phormidium autumnale extract with different polarities, it is crucial to choose the appropriate method for evaluating the antioxidant potential, and to investigate the antioxidant mechanism developed by each structure of the molecule. A total of eleven chlorophyll compounds were separated on biomass Phormidium autumnale the photosynthetic culture. Among the major compounds found chlorophyll a (1498.40μg / g) and pheophytin b (613.23μg / g), where the total chlorophyll pigments totaled 2720.19μg / g in the biomass extract. The potential for scavenging free radicals was examined by two different methods with regard to their polarity, being that for the lipophilic method of the Phormidium extract autumnale proved to be 200 times more potent than α-tocopherol at the disposal of peroxyl radicals , and the method the hydrophilic Phormidium autumnale extract showed antioxidant activity of 219.82 mu equivalent Trolox / g extract. Finally, we note that the biomass Phormidium autumnale has considerable potential in the production of chlorophyll compounds in phototrophic conditions, proving to be an alternative source to conventional arrays of chlorophyll pigments and proved efficient in eliminating free radicals, showing their potential bioactive .